2013
DOI: 10.1111/jdi.12097
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon and insulin have opposite effects on tissue chromium distribution in an obese mouse model

Abstract: Aims/Introduction: Previous studies have suggested that chromium (Cr) is an essential cofactor for normal carbohydrate metabolism and affects insulin sensitivity, especially in rodent models. Several factors, such as insulin challenge, high carbohydrate intake, and response to stress (e.g., in obesity), alter Cr excretion or distribution. Glucagon is known to regulate carbohydrate metabolism and hyperglucagonemia plays a role in the development of hyperglycemia in diabetic subjects. Materials and Methods: In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…For essential metals, the bone is a physiological storage pool [4]. Chromium is released from bones and moved by the bloodstream into mobilizable pools, including the muscle, liver, and fatty tissues, which contribute to activating insulin signaling to reduce blood glucose levels [28]. Consistent with these observations, exercise promoted the movement of chromium from storage pools into glucose metabolic tissues.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…For essential metals, the bone is a physiological storage pool [4]. Chromium is released from bones and moved by the bloodstream into mobilizable pools, including the muscle, liver, and fatty tissues, which contribute to activating insulin signaling to reduce blood glucose levels [28]. Consistent with these observations, exercise promoted the movement of chromium from storage pools into glucose metabolic tissues.…”
Section: Discussionmentioning
confidence: 82%
“…These mice were grouped and fed a standard diet a high-fat diet (HFD, diet 592Z, 20.4% protein-enriched diet and modified Lab w/35.5% Lard, 1.12 ppm Cr, metabolizable energy 4.5 kcal/gm, PMI Nutrition International Inc., MO, USA) (Table S2) for 12 weeks. Generally, mice were fed a high-fat diet for 4 weeks to obtain a diet-induced obesity model [28]. Mice were housed individually in microisolation cages on high-efficiency particulate air filtered ventilated racks (Rungshin IVC Systems, Taichung, Taiwan) with a controlled temperature (22 ± 1 • C), humidity (55 ± 5%), along with a 12 hr light/dark cycle.…”
Section: Animals and Dietmentioning
confidence: 99%
“…All feeding was ad libitum. Four weeks of an HFD are generally required to achieve a diet‐induced obesity model 22,23 . All mice were kept in the animal quarters,here, each mouse was provided an individual microisolation cage, which was placed on racks ventilated using high‐efficiency particulate air filters (Rungshin IVC Systems).…”
Section: Methodsmentioning
confidence: 99%
“…Four weeks of an HFD are generally required to achieve a diet-induced obesity model. 22,23 All mice were kept in the animal quarters,here, each mouse was provided an individual microisolation cage, which was placed on racks ventilated using high-efficiency particulate air filters (Rungshin IVC Systems). In the quarters, we applied a 12:12-h light-dark cycle, while maintaining the temperature at 22°C ± 1°C and humidity at 55% ± 5%.…”
Section: Animals and Drug Treatmentmentioning
confidence: 99%
“…Studies have shown that Cr 3+ and its complex can decrease fasting blood glucose level [12][13][14][15] . Cr can enhance insulin sensitivity and regulate lipid metabolism in diabetes 9,[16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%